Creatinephosphokinase in organophosphorus poisoning - Kumar, Amith; V., Virupakshappa (International Journal of Advances in Medicine, 2017)
Background: Organophosphorus Poisoning has been found to be a major cause of death or morbidity in our country as it freely available without need of prescription unlike in developed countries where prescription is required to purchase insecticides, the various organophosphorus compounds available are Malathion, parathion, diazinon, fenthion, dichlorvos, chlorpyrifos, ethion. Erythrocyte cholinesterase (EchE) and pseudocholinesterase (Butyryl cholinesterase-BchE) are markers used for assessing the severity in OP poisoning, but estimation of these are costly, has variable values for different individuals and is not available at all centers. This study was done to estimate levels of serum Creatine Phosphokinase (CPK)serially in acute OP poisoning patients and to correlate with prognosis. Methods: 50 patients of organophosphorus poisoning admitted to Mcgann hospital attached to Shimoga institute of medical sciences Shimoga over a period of 6 months from 1st July 2016 to 31st December 2016 were taken up for the study. A comprehensive history and detailed clinical examination was performed and patients were clinically evaluated for severity. Level of serum cholinesterase and serum CPK were estimated at admission and CPK level was measured on day 3 and day 5. The outcome of these patients was evaluated. Results: Out of 50 patients, 78% (n=39) were males and 22% (n=11) were females. Majority of patients were in the age group 21 – 40 years. Chlorpyrifos was the most common compound used. 72% had mild, 20% had moderate and 8% had severe poisoning. Serial measurements of serum CPK levels showed significant correlation with the severity of acute OP poisoning patients. The CPK levels showed a sensitivity of 74% and a specificity of 81% with a positive predictive value of 92%. Conclusions: Severe organo phosphorus poisoning is correlated with CPK levels. This study recommends CPK level estimation in assessment of severity and prognosticate patients with organophosphorus compound as alternate marker to choline esterase.